Quality of life in hypertensive patients using the WHOQOL-BREF instrument in the post-pandemic Bangladesh: A cross-sectional study - Nasrin Akter; Farhana Faruque Zerin; Bilkis Banu; Fatema Afrin Kanta; Shahnaz Begam; Sarder Mahmud Hossain (PLoS ONE, 2026)
Background To combat growing prevalence of hypertension in Bangladesh, it is critical to have an in-depth understanding about quality of life (QOL) among people living with hypertension and related factors. In the recent COVID-19 pandemic the QOL of hypertensive people got downsized. This study aimed to measure QOL among hypertensive people in a selected tertiary hospital in Dhaka city, and its association with the basic characteristics of the patients. Methods This study was conducted among randomly selected 300 hypertensive patients from two departments of Square Hospitals Limited, using the patient register record. Data were collected through face-to-face interview methods. The WHOQOL-BREF questionnaire was used to assess the QOL of the subjects. Descriptive statistics were used to examine mean scores of quality of life. Cronbach’s alpha coefficient and Pearson’s correlation coefficient were applied to estimate the internal consistency, and the level of agreement among different domains of WHOQOL-BREF, respectively. Chi-square test followed by binary regression analysis was used to measure the association between QOL domains and independent variables. Results Both overall WHOQOL-BREF and each domain had a good internal consistency, (r = 0.13–0.77, p < 0.01). The QOL among hypertensive patients was found poor in psychological (71%) and social (74.7%) domain and good in environment (63%) and physical (65%) domain. Backward binary regressions revealed that being older over 55 years (p = 0.01), diabetic (p = 0.02), having history of COVID-19 (p = 0.01) and poor monthly family income (USD ≤ 853.14) (p = 0.01) were significantly associated with poor QOL in all domains. Moreover, older age (p = 0.01) and poor lifestyle (p = 0.02) were significantly associated with poor overall quality of life and poor perception of general health. Conclusion The results revealed low QOL in psychological and social domain, including significant factors associated with the poor QOL in all domains. Planning and implementation of effective interventions are needed to improve QOL among hypertensive patients targeted towards aged, diabetic, lower income group who had positive COVID-19 infection and poor lifestyle through health system strengthening.